A Nitric Oxide Storage and Transport System That Protects Activated Macrophages from Endogenous Nitric Oxide Cytotoxicity - Lok, Hiu Chuen (J Biol Chem, 2016)
Nitric oxide (NO) is integral to macrophage cytotoxicity against tumors due to its ability to induce iron release from cancer cells. However, the mechanism for how activated macrophages protect themselves from endogenous NO remains unknown. We previously demonstrated by using tumor cells that glutathione S-transferase P1 (GSTP1) sequesters NO as dinitrosyl-dithiol iron complexes (DNICs) and inhibits NO-mediated iron release from cells via the transporter multidrug resistance protein 1 (MRP1/ABCC1). These prior studies also showed that MRP1 and GSTP1 protect tumor cells against NO cytotoxicity, which parallels their roles in defending cancer cells from cytotoxic drugs. Considering this, and because GSTP1 and MRP1 are up-regulated during macrophage activation, this investigation examined whether this NO storage/transport system protects macrophages against endogenous NO cytotoxicity in two well characterized macrophage cell types (J774 and RAW 264.7). MRP1 expression markedly increased upon macrophage activation, and the role of MRP1 in NO-induced (59)Fe release was demonstrated by Mrp1 siRNA and the MRP1 inhibitor, MK571, which inhibited NO-mediated iron efflux. Furthermore, Mrp1 silencing increased DNIC accumulation in macrophages, indicating a role for MRP1 in transporting DNICs out of cells. In addition, macrophage (59)Fe release was enhanced by silencing Gstp1, suggesting GSTP1 was responsible for DNIC binding/storage. Viability studies demonstrated that GSTP1 and MRP1 protect activated macrophages from NO cytotoxicity. This was confirmed by silencing nuclear factor-erythroid 2-related factor 2 (Nrf2), which decreased MRP1 and GSTP1 expression, concomitant with reduced (59)Fe release and macrophage survival. Together, these results demonstrate a mechanism by which macrophages protect themselves against NO cytotoxicity.